Paradise and Power : American and Europe in the New World Order - Kagan, Robert (London Atlantic Books, 2004)
Europe sees the United States as high-handed, unilateralist, and unnecessarily belligerent; the United States sees Europe as spent, unserious, and weak. The anger and mistrust on both sides are hardening into incomprehension.".
Keywords: Post-communism -- United States -- Europe